(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper examines the role of digital technologies in language learning, focusing on the impact of mobile applications, web-based platforms, and AI-powered tools. The integration of mobile apps, online learning spaces, intelligent tutoring systems, and digital tools complements traditional language learning methods and supports learners in developing key language skills. Through a survey conducted among university students, this study investigates the effectiveness, benefits, and challenges of digital learning tools. The findings reveal that while these technologies enhance learning by offering convenience and instant feedback, they also present limitations such as reduced opportunities for real-life speaking practice and difficulties in maintaining motivation.